Novel compound heterozygous PIEZO1 variants in dehydrated hereditary stomatocytosis initially suspected as myelodysplastic syndromes: a case report - Sun, Yongcheng; Wang, Tao; Wang, Shuyan; Chen, Yan; Xu, Zhijuan; Shi, Cong; Wang, Zanzan; Ouyang, Guifang (Frontiers in Oncology, 2025)
IntroductionDehydrated hereditary stomatocytosis (DHS) is a rare autosomal dominant congenital non-immune hemolytic anemia caused by pathogenic variants in the PIEZO1 gene. Its clinical presentation often overlaps with other hematological disorders, leading to diagnostic challenges and potential mismanagement.Case presentationA 22-year-old man presented with a 7-year history of anemia initially misdiagnosed as myelodysplastic syndrome (MDS) due to hypercellular bone marrow findings and MDS-like features. Over time, his condition progressed to include cerebral venous sinus thrombosis (CVST), a severe complication. Comprehensive genetic testing at our hospital using whole-exome sequencing (WES) revealed novel compound heterozygous PIEZO1 variants: NM_001142864.4: c.6622A>G (p.Ile2208Val) and NM_001142864.4: c.3160C>A (p.Leu1054Met). These findings confirmed the diagnosis of DHS. The patient underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT), resulting in resolution of his hematological abnormalities and symptoms.ConclusionThis case underscores the importance of considering DHS in patients with unexplained anemia and MDS-like features, particularly when associated with thrombotic complications. It highlights the critical role of genetic testing in diagnosing rare hereditary anemias and demonstrates that allo-HSCT can be a curative treatment in selected cases.